Characteristics of vanadium adsorption on and desorption from humic acid. Issue 6 (3rd July 2018) - Yu, Yaqi; Liu, Meng; Yang, Jinyan
ABSTRACT: Information about geochemical behaviour of vanadium in soil to date is very limited. This study explored the characteristics and factors that affect vanadium adsorption-desorption by humic acid (HA) which was extracted from red soil. Fourier-transform infrared analysis illustrated that various functional groups on HA participated in vanadium adsorption. Monolayer vanadium adsorption at certain range of HA concentrations was detected, and main adsorption-desorption controlling step was chemical reactions. The adsorption-desorption was strongly dependent on HA concentration, solution pH and coexisting anion species. The main existing form and valence of vanadium at different solution pH, HA and vanadium concentration predominantly contributed to the variable vanadium adsorption ability. The presence of, Cl −, and had insignificant effect ( p  > 0.05) on adsorption, whereas, , , and significantly promoted ( p  < 0.05) the adsorption. Similarly, and significantly increased ( p  < 0.05) the desorption. The maximum adsorption amount was 19.2 mg g –1 by 0.727 g L –1 HA at the initial vanadium(V) concentration of 182 mg L –1, and the corresponding desorption rate was 9.44%, indicating that HA can fix vanadium in soil to a certain degree and may thus reduce bioavailability and toxicity of vanadium, which is important to keep the ecological dynamic balance.